(3QSGdI GdZQHI GdeZQjHIs - (3jMji Hf qMnHT Hf CejQc, CHh GdaJhM, TgGH GdOjf, GdSgQhQOj,J (B587 (3g` s ((3GdfLa s)
(3ChdgG (B:s
(3CeG HYO aEfi deG QCjJ bUI Mi Hf jbXGf UGOaJgG eY eG ajgG ef YLGFH GdcdeGJ s
(3BNQgG (B:s
(3hSbWJ ef GdghGA Edi GdgGhjI Hfi bhekG djShG HeDefjf s
(3HgG fXGe GdJYbjHIs
(3cJHJ gPg GdfSNI ef fSNI HNW TgGH GdHMQGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B140 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B189s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B877s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs